A comparative DFT study of Fe3+ and Fe2+ ions adsorption on (100) and (110) surfaces of pyrite: An electrochemical point of view. (16th December 2019) - Nourmohamadi, Hossein; Aghazadeh, Valeh; Esrafili, Mehdi D.
Abstract : Pyrite acts as a catalyst in the mineral processing, and the speed of ferric ion reduction and mineral decomposition increases with increasing cathodic points. In this study, the ferric ion interaction on the (100) and (110) surfaces of pyrite was studied using the density functional theory calculations. The analysis of stability, density of states, and electron density were performed to understand the interaction between the ferric ion and pyrite surfaces. The results showed that pyrite surface is chemically active and tends to absorb ferric ion between two surface sulfur atoms. The hyperconjugation between the 3d orbital of ferric ion and the 3p or 3d orbitals of surface atoms provides the conditions for the Fe 3+ ion adsorption. The molecular orbital (MO) and electron density analyses indicate that the 3p orbitals of S atoms play a more important role in bonds formations relative to the 3d orbitals. The (110) surface is more active, and the adsorption energy is larger than that of surface (100), which is the result of decreased cation coordination and the presence of sulfur at the surface. Subsequently, the interaction of the Fe 2+ ion, as product of Fe 3+ ion reduction and its competitor for adsorption, on the surfaces was studied. The Fe 2 + ion adsorbs stronger at the surface of (110), and the adsorption energies at (100) and (110) surfaces were obtained as −24 and −47 kcal/mol, respectively. In general, the Fe 3+ ion is a stronger oxidizing agent than Fe 2+ on pyrite surfaces.